Auto-generation of advanced control algorithms' code for microcontrollers using transcompiler - Chaber, Patryk; Lawrynczuk, Maciej (2016 21st International Conference on Methods and Models in Automation and Robotics (MMAR), 2016)
This paper presents a new approach to automatic code generation of advanced control algorithms, primarily model predictive control schemes, for microcontroller-based embedded systems. The main part of the developed tools, the transcompiler, makes it possible to effectively translate the algorithms described in a high-level language (MATLAB) into C language code for the chosen hardware platform. Implementation of two control algorithms using the described approach for the STM32 microcontroller is reported, results of the real experiments are discussed.